Surface properties of binary blend films of poly(N-vinyl-2-pyrrolidone) and poly(vinyl alcohol) with sodium alginate - EROĞLU, MEHMET SAYIP (JOHN WILEY & SONS INC, 2006)
Blends of poly(N-vinyl-2-pyrrolidone) (PVP) and poly(vinyl alcohol) (PVA) with sodium alginate (NaAlg) were prepared via casting from aqueous solutions. All the obtained blend films were optically clear to the naked eye. The surface properties of the films were analyzed by atomic force microscopy (AFM) and contact-angle measurements. The surface free energy components of the blend films were calculated from contact-angle data of various liquids with the Van Oss-Good methodology. It was determined that both the Lifshitz-van der Waals component and the electron-donor component of the surface free energy of the blend films decreased with an increase in the NaAlg content to a considerable extent. However, the electron-acceptor component of these blends increased with increasing NaAlg content. The surfaces of both the PVP/NaAlg and PVA/NaAlg blends were enriched in the low surface free energy component, that is, NaAlg. This conclusion was further confirmed by AFM image observation of the surface morphology of these blends. (c) 2005 Wiley Periodicals, Inc.
Keywords: blends; compatibility; contact angles; miscibility; sodium alginate; surface energy; FREE-ENERGY ANALYSIS; DELIVERY